2010
DOI: 10.1007/s10461-010-9773-1
|View full text |Cite
|
Sign up to set email alerts
|

Male to Female and Female to Male Transgender Persons have Different Sexual Risk Behaviors Yet Similar Rates of STDs and HIV

Abstract: The epidemiology of STDs and HIV among male-to-female (MTF) and female-to-male (FTM) transgender persons is limited, which makes prevention for transgender populations challenging. We examined data collected at visits for all self-identified MTF and FTM patients at the municipal STD clinic in San Francisco from January 1, 2006 to December 31, 2009. We compared demographic and socio-behavioral characteristics, as well as STD and HIV positivity and history of previous STD. Despite demographic and behavioral risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 7 publications
0
44
0
1
Order By: Relevance
“…Many transmen/trans-masculine people have had unprotected sex with men without knowing the partner's serostatus and utilize the Internet to find sexual partners (Reisner et al, 2009). Stephens, Bernstein, and Philip (2010) found when examining records from the San Francisco municipal STD clinic no difference between transmen/trans-masculine people and transwomen/trans-feminine people in regard to HIV or STD status. The researchers also found that 23% of the transmen/trans-masculine people were involved in exchange sex.…”
Section: Hiv/aidsmentioning
confidence: 99%
“…Many transmen/trans-masculine people have had unprotected sex with men without knowing the partner's serostatus and utilize the Internet to find sexual partners (Reisner et al, 2009). Stephens, Bernstein, and Philip (2010) found when examining records from the San Francisco municipal STD clinic no difference between transmen/trans-masculine people and transwomen/trans-feminine people in regard to HIV or STD status. The researchers also found that 23% of the transmen/trans-masculine people were involved in exchange sex.…”
Section: Hiv/aidsmentioning
confidence: 99%
“…This research has mainly focused on transgender women, but Stephens, Bernstein and Philip (2010), in a study in San Francisco, USA, found no difference in rates of sexually transmitted infections and HIV between transgender men and transgender women. In contrast, Herbst, Jacobs, Finlayson, McKleroy, Neumann and Crepaz (2008) found low rates of HIV among transgender men in their review of studies of transgender HIV risk in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…However, 42 (32.3%) of the 130 newly diagnosed HIV cases among transgender people occurred in transgender men. In a US study, HIV infection rates were similar for transgender men (10%) and transgender women (11%) [23].…”
Section: Discussionmentioning
confidence: 99%